Financialization of Companies in the Global Market - Ronza, Luigi di (Richtmann Publishing, 2011)
The purpose of this article is to analyze the role of finance within the corporate strategy. In dealing with the process of geographical decentralization of the activities of the value chain, every company is in contact with different areas, each of which may require different ways of interaction. The interaction can take place with the creation of a constructive dialogue between stakeholders with different cultures and behavior and may allow the central structure to assess the exact dynamics of local situations and to improve the dynamics of financial processes, so over time the finance function has changed its purpose considering the overall uncertainty and specificity of local.